Towards improved visual stimulus discrimination in an SSVEP BCI - Hodgskiss, Dean Leslie (Division of Biomedical Engineering, 2015)
The dissertation investigated the influence of stimulus characteristics, electroencephalographic (EEG) electrode location and three signal processing methods on the spectral signal to noise ratio (SNR) of Steady State Visual Evoked Potentials (SSVEPs) with a view for use in Brain-Computer Interfaces (BCIs). It was hypothesised that the new spectral baseline processing method introduced here, termed the 'activity baseline', would result in an improved SNR.